Rubber, rubber and rubber: How 75 years of successive rubber plantation rotations affect topsoil quality?. (5th April 2022) - Panklang, Phantip; Thoumazeau, Alexis; Chiarawipa, Rawee; Sdoodee, Sayan; Sebag, David; Gay, Frédéric; Thaler, Philippe; Brauman, Alain
Abstract: Rubber tree plantations ( Hevea brasiliensis ) cover large areas in the tropics. In historical producing regions like South Thailand, rubber has been planted by smallholders for three successive rotations lasting a total of 75 years. Despite possible consequences on topsoil, the long‐term impacts of repeated rubber plantations on soil quality remain unknown. This study aims to better understand how various factors linked to long‐term rubber land use and land use change affect topsoil physico‐chemical properties and soil organic carbon (SOC) thermal stability. We focus on the effects of three factors: i. deforestation (change from forest to first rubber plantation); ii. the age of the rubber stand (immature vs. mature); and iii. long‐term rubber cultivation (first, second or third successive rotation) over a chronosequence in farmers plots. Our results show that soil was deeply degraded after deforestation to a rubber plantation. Long‐term rubber cultivation is also detrimental for the soil and has a more negative impact on soil physico‐chemical properties and carbon dynamics, than the age of the rubber stand (e.g., on average, decrease of 50% of SOC content between forest and third rotation). At the third rotation, after 50 years of rubber cultivation, the quality of the 0–10 cm soil layer was very low, with an increase in SOC thermal stability. At this stage, logging practices upset the sustainability of the system. These impacts could be limited by less destructive practices during planting.